Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4269/ajtmh.14-0346
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Associated with Schistosomiasis Before and After Treatment in Young Children in Rusinga Island, Western Kenya

Abstract: Abstract. Schistosoma mansoni infection is a major cause of organomegaly and ultimately liver fibrosis in adults. Morbidity in pre-school-aged children is less defined, and they are currently not included in mass drug administration (MDA) programs for schistosomiasis control. We report results of a study of the association of schistosomiasis with organomegaly in a convenience sample of 201 children under 7 years old in Rusinga, Kenya on two cross-sectional visits, before and after praziquantel treatment. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 44 publications
2
44
3
Order By: Relevance
“…It seemed to decrease; however, it has not decreased significantly when compared to the prevalence reported by previous studies in Mbita district [2527]. Re-infection rate reported in previous studies in Kenya were 43.8%, 45 days after treatment, with a baseline prevalence of 84% [31], 34.4%, three to four months after treatment, with a baseline prevalence of 44.9% [32], and 8.6%, eight weeks after treatment, with a baseline prevalence of 47.4% [33]. Therefore, the 36% prevalence in the second year of the study, which was conducted six months after MDA with praziquantel, signifies that the re-infection rate in this area remained relatively high although cure rate after MDA was not examined.…”
Section: Discussionmentioning
confidence: 68%
“…It seemed to decrease; however, it has not decreased significantly when compared to the prevalence reported by previous studies in Mbita district [2527]. Re-infection rate reported in previous studies in Kenya were 43.8%, 45 days after treatment, with a baseline prevalence of 84% [31], 34.4%, three to four months after treatment, with a baseline prevalence of 44.9% [32], and 8.6%, eight weeks after treatment, with a baseline prevalence of 47.4% [33]. Therefore, the 36% prevalence in the second year of the study, which was conducted six months after MDA with praziquantel, signifies that the re-infection rate in this area remained relatively high although cure rate after MDA was not examined.…”
Section: Discussionmentioning
confidence: 68%
“…However, recent research has shown that first infection is often acquired at a very young age, 4 8 and there is growing evidence that the burden of disease among PSAC may warrant global attention. Although schistosomiasis-associated morbidity among PSAC is still not well defined, documented effects include fecal occult bleeding, 9 , 10 anemia, 11 , 12 and ultrasound abnormalities 13 ; however, discriminating these symptoms from other potential infectious causes remains a challenge. Despite mounting evidence for the need, PSAC are not routinely screened or included in schistosomiasis mass treatment programs in large part due to the need for better diagnostic tools and the lack of a pediatric formulation of PZQ.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reported lower worm fecundity in the endemic area than the epidemic area, as would be expected if worm fecundity declines with worm age. A recent study failed to find evidence of overshoot in children under age seven (77), which suggests that young children might harbor younger, highly fecund worms than older hosts, providing further evidence for reproductive senescence. Finally, in areas of low prevalence, many humans harbor worms, but shed eggs at levels undetectable by urine filtration or stool assay (52).…”
Section: Discussionmentioning
confidence: 98%